ANALISIS PARTISIPASI MASYARAKAT KOTA SURAKARTA DALAM PEMILIHAN WALIKOTA SURAKARTA TAHUN 2020 DALAM PRESPEKTIF NEGARA DEMOKRASI - Mahendra, Halim Arrosyid; Riewanto, Agus (Res Publica: Jurnal Hukum Kebijakan Publik, 2024)
ABSTRACTThis research aims to examine community participation in the 2020 Surakarta Mayoral Election with a Democratic State perspective and knowing the obstacles related to community participation. This legal study is a descrptive study of empiric law. The approach used is a qualitative approach. The data sources used consist of primary data and secondary data. The technique of collecting legal materials with interview methods. Technical analysis used is Interactive Model Analysis methods. The results of the study indicate that community participation in the 2020 Surakarta Mayoral Election has decreased due to the co-19 pandemic, the lack of public response to the online system and the apathetic behavior of the people themselves. It is hoped that the socialization regarding the online mayoral election conducted by the KPU will innovate more so that people will become interested and willing to exercise their voting rights, and the community will be more adaptable to online activities so that the level of community participation will be high even in the midst of a pandemic.